2020
DOI: 10.1093/clinchem/hvaa013
|View full text |Cite
|
Sign up to set email alerts
|

High-Accuracy Determination of Microsatellite Instability Compatible with Liquid Biopsies

Abstract: Background Microsatellite instability (MSI) has recently emerged as a predictive pan-tumor biomarker of immunotherapy efficacy, stimulating the development of diagnostic tools compatible with large-scale screening of patients. In this context, noninvasive detection of MSI from circulating tumor DNA stands as a promising diagnostic and posttreatment monitoring tool. Methods We developed drop-off droplet-digital PCR (ddPCR) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 23 publications
2
43
0
Order By: Relevance
“…To our knowledge, only a few studies have reported data on ctDNA in endometrial cancer [ 11 16 , 24 ]. CtDNA was detected preoperatively in 15% (10/68 patients) to 41% (21/51 patients) of patients with endometrial cancer, using tumor-associated mutations [ 12 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only a few studies have reported data on ctDNA in endometrial cancer [ 11 16 , 24 ]. CtDNA was detected preoperatively in 15% (10/68 patients) to 41% (21/51 patients) of patients with endometrial cancer, using tumor-associated mutations [ 12 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total plasma cell-free DNA (cfDNA) levels in endometrial cancer patients were reported to be increased compared to healthy controls [ 9 , 10 ], but lacks specificity to robustly discriminate pathological levels versus benign controls. A few studies have evaluated the feasibility of using tumor-specific mutations to detect ctDNA in the plasma of endometrial cancer patients [ 11 16 ]. In particular, ctDNA screening for point mutations present in primary gynecological tumors using digital droplet PCR reported promise for detecting recurrence preceding anatomic findings on standard computed tomography scans by an average of 7 months [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) (evaluation of MMR protein expression including MLH1, MSH2, MSH6 and PMS2) and pentaplex PCR-based assays (directed against 5 microsatellite regions including at least BAT-25 and BAT-26 mononucleotide markers such as Promega MSI Analysis System) are currently the reference assays recommended for dMMR/MSI testing 9 , 27 – 29 . However, novel molecular-based methods emerge for the detection of MSI, including different real-time PCR and droplet digital PCR (ddPCR)-based methods 30 33 as well as various custom Next-Generation Sequencing (NGS) approaches 34 43 . In this study, we aimed to evaluate the performance of 3 molecular assays, including a custom capture-based NGS approach, Idylla MSI and Bio-Rad ddPCR MSI assays, for the determination of MSI status for theranostic purposes in patients with endometrial and colorectal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…With a 100% sensitivity and specificity, the Bio-Rad ddPCR MSI assay consists in a fast and cost-effective multiplex assay compatible with large-scale testing of patients, though requiring a specialized laboratory to interpret the data. In a recent study, a custom implementation of ddPCR using specialized targets allowed to reach an unmatched sensitivity for MSI screening compared to previously used approaches, making this methodology applicable for MSI analysis in liquid biopsies 30 .…”
mentioning
confidence: 99%
“…Immunotherapy is a well-established therapeutic option for MMR-deficient mCRC [ 3 , 4 ]. While few studies reported >98% accuracy of ctDNA MMR-deficient noninvasive identification, an ongoing prospective trial (NCT03594448) is investigating serial LB as a detection method for MMR-deficient mCRC [ 107 , 108 ].…”
Section: Molecular Profiling and Monitoring Of Resistance Mechanisms Through Lbmentioning
confidence: 99%